A heterogeneous catalyst from a mixture of coconut waste and eggshells for biodiesel production - Sulaiman, Sarina; Ruslan, Norbaiduri I F (Taylor and Francis Ltd., 2017)
In this study, heterogeneous catalysts were synthesized from mixture of calcined solid coconut waste and eggshells as a catalyst for the transesterification of palm oil. Response surface methodology (RSM) based on central composite design (CCD) was used to optimize the amount of catalysts (coconut waste:calcined eggshells ratio) for production of biodiesel. The optimum ratio of catalysts for biodiesel production was found as follows: coconut waste to eggshell, 5:1 wt% and the highest FAME yield was 81% with fixed parameters of reaction time (3 h), reaction temperature (65°C), and methanol:oil ratio (24:1).